An audit of surgical repair of Tetralogy of Fallot in an African tertiary care centre - Ngwezi, Deliwe P.; Vanderdonck, Katharina; Levin, Solomon E.; Cilliers, Antoinette (SA Heart Journal, 2017)
Background: For patients undergoing Tetralogy of Fallot (TOF) repair at institutions in sub-Saharan Africa, data on type of surgical repair, operative mortality and important determinants of outcome such as age at operation and development of pulmonary regurgitation (PR) post-repair is scanty. Objective: To describe the outcomes of children diagnosed with TOF who underwent surgical repair at our center with emphasis on post-operative PR. Methods: This was a retrospective cohort study undertaken from 1 January 1994 to 31 December 2003 at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). The descriptive analysis of the clinical audit was done in 2010. Results: Fifty four (75%) patients were operated upon: 50 (92.5%) had complete repair and 4 (7.4%) had a palliative procedure in the form of a Blalock-Taussig (B-T) shunt. The median age for corrective surgery was 39.5 months. Twenty out of 50 (40%) patients had simple repair, 10 (20%) had repair which included pulmonary valvotomy, 15 (30%) had a transannular patch (TAP) repair with or without monocusp and 5 (10%) had conduit insertion. An evaluation of severe PR among all the repair groups in the immediate post-operative period (<1 year) revealed that 5 out of 15 (33.3%) patients who had TAP repair developed severe PR, whilst no severe PR was noted in the simple, pulmonary valvotomy and conduit repair groups. During the intermediate post-operative period (1 - 5 years), severe PR was documented in 4 (27%) patients with TAP repair, 2 (10%) with simple repair and 2 (20%) in the pulmonary valvotomy group only. In the long term period (>5 years), severe PR was documented in 3 (30%) patients with pulmonary valvotomy, 8 (53%) who had TAP repair, 2 (10%) patients with simple repair including 1 (20%) patient with a xenograft conduit. One out of 50 (2%) surgically corrected patients who had a complex anatomy died in the immediate post-operative period. Twenty eight out of 50 (56%) patients who had complete correction were lost to follow-up. Conclusion: Surgical correction occurs much later in infancy and childhood compared to developed countries. Severe PR is a serious complication strongly associated with all types of surgical repair of TOF and these patients require lifelong follow-up. Despite the small sample size, the operative mortality compares favourably to fi rst world centers.